2002
DOI: 10.1038/sj.bjc.6600218
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of DNA mismatch repair-deficient and -proficient tumour cells

Abstract: Loss of DNA mismatch repair is a common finding in hereditary nonpolyposis colon cancer as well as in many types of sporadic human tumours. DNA mismatch repair-deficient cells have been reported to be resistant to many chemotherapeutic agents and to radiotherapy, and to have the potential of rapidly acquiring additional mutations leading to tumour progression. Photodynamic therapy is a new treatment modality using light to activate a photosensitiser that preferentially localises in tumour cells. An oxygen depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This effect was not observed in MMR-deficient cells, in which APC action prevailed. These data are in agreement with the increased CFS expression after replicative stress that was reported in RAD51-depleted MCF-7 breast cancer cells [11], which also happen to be MMR-proficient [54].…”
Section: Discussionsupporting
confidence: 92%
“…This effect was not observed in MMR-deficient cells, in which APC action prevailed. These data are in agreement with the increased CFS expression after replicative stress that was reported in RAD51-depleted MCF-7 breast cancer cells [11], which also happen to be MMR-proficient [54].…”
Section: Discussionsupporting
confidence: 92%
“…For example, it has been reported that the oxidized nucleoside triphosphate pool is a significant contributor to genomic instability in mismatched repair-deficient cells (25,26). However, this situation is unlikely for MCF-7 cells because there are reports of mismatch repair proficiency for these cells (27)(28)(29).…”
mentioning
confidence: 91%
“…PDT can inactivate antibiotic-resistant microbial pathogens and has the potential to become an efficient alternative treatment modality for microbial infections [9]. In the field of oncology, PDT has become a promising modality for the treatment of a variety of solid tumors [10] and presents an alternative treatment option for tumors resistant to chemo-and/or radio-therapy [11,12]. For the treatment of microbes, PDT is also effective for some localized microbial infections, such as oral candidosis, periodontitis or chronic wounds [13,14], but its usefulness is not yet fully established.…”
Section: Introductionmentioning
confidence: 99%